1 Answer | Add Yours
You should remember the equation of circle in standard form such that:
`(x-h)^2 + (y-k)^2 = r^2`
The problem provides the coordinates (h,k) of center of circle, hence, you should substitute 3 for h and -1 for k in equation above such that:
`(x-3)^2 + (y+1)^2 = r^2`
Notice that the radius is not given but you may find it using the information provided by the problem.
The line that has the equation `2x - 5y + 18 = 0` and the length of 6 represents a chord of circle.
You may drop a perpendicular from the center of circle to this chord. The perpendicular line drops in the middle of this chord.
You may find the length of perpendicular using the formula:
`d = |a*x_C + b*y_C + c|/(sqrt(a^2+b^2))`
Notice that ax+by+c represents the equation of chord and `x_C,y_C` , coordinates of the center.
`d = |6 +5 + 18|/(sqrt(4+25))`
`d = |29|/(sqrt(29)) =gt d = sqrt29`
Notice that the radius of circle represents the hypotenuse of right angle triangle that has the lengths of the legs `sqrt29` and 3.
Using Pythagorean theorem yields:
`r^2 = 29 + 9`
`r^2 = 38`
You may now write the equation of the circle such that:
`(x-3)^2 + (y+1)^2 = 38`
Hence, evaluating the equation of circle under given conditions yields `(x-3)^2 + (y+1)^2 = 38.`
We’ve answered 318,989 questions. We can answer yours, too.Ask a question